2002
DOI: 10.1038/sj.sc.3101311
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality of life of persons with spinal cord injury: external and structural validity

Abstract: Study design: Measurement evaluation of the external and structural components of validity. Objectives: To examine the relationships between quality of life (QOL) as measured by the spinal cord injury (SCI) version of the Ferrans and Powers Quality of Life Index (QLI) and other constructs represented within the model of disablement; and to examine the domains and scoring model of the QLI by exploring item and overall score/section score relationships. Setting: Community, Alberta, Canada. Methods: A convenience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 36 publications
3
58
0
1
Order By: Relevance
“…3,4,[58][59][60][61]70,71,[86][87][88][89][90][91][92][93] In this study, it was impossible to differentiate the notion of social activities from the dual concepts of 'relationships' and 'doing'. When the participants spoke of their relationships with families and friends it was frequently in the context of activities: travelling, going out to restaurants, bars, theatres, concerts, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,[58][59][60][61]70,71,[86][87][88][89][90][91][92][93] In this study, it was impossible to differentiate the notion of social activities from the dual concepts of 'relationships' and 'doing'. When the participants spoke of their relationships with families and friends it was frequently in the context of activities: travelling, going out to restaurants, bars, theatres, concerts, etc.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, although survival rates are increasing among those people who have the highest cord lesions (C4 and above), 5,6 a review of the research literature demonstrated that little effort has been expended to determine whether those people who have the most profound degrees of impairment feel satisfied with their lives or perceive their survival to be worthwhile (see Hammell's 7 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, while the need to understand more about the perceptions and determinants of life's quality held by people with SCI is undisputed, there have been difficulties in studying a concept that lacks a clear definition and that is perceived differently by different people, in differing circumstances and at different times of their lives. 3,4 The vast majority of research into QOL following SCI has adopted a quantitative approach, 3 reflecting researchers' assumptions that quality can be measured quantitatively; that the determinants of QOL following SCI can be reliably predicted by able-bodied researchers; and that the subjective experience of a life can be objectively and accurately discerned by another person.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 During the past few decades, advances in medical care are enabling persons with SCI to survive the initial injury and to prolong their life expectancy post-SCI. 3 The need for outcome measures assessing health and QOL after rehabilitation is, therefore, becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%